From petri net based PLCs to knowledge based control - Atabakhche, H
Within the context of Programmable Logic Controllers (PLCs) and their application in controlling complex discrete systems such as FMS, two different new approaches are being developed. One is based on Petri net for modeling and implementing sequential control, the other employs Artificial Intelligence techniques for scheduling and monitoring. Sometimes the two approaches are presented as separate but complementary techniques in which case two separate programming tools are proposed. The aim of this paper is not only to show that the two approaches are complementary, but also to explicit the fact that they are strongly similar and can be utilized together when a "token player" (Petri net interpreter) is used for the implementation. In fact, a "token player" interpreting a Petri net based specification can be seen as an elementary knowledge based deduction system.